Analysis of Flavonoid Contents in Coffee Mistella (Dendrophthoe pentandra (L.) Miq.) Using Thin Layer Chromatography-Densitometry Techniques - Saputri, Nora Dwi; Adiwinata, I Nyoman; Muflihah, Yeni Maulidah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
Flavonoids, a class of phenolic compounds widely distributed in plants, are present in the coffee mistletoe Dendrophthoe pentandra (L.) Miq. The extraction of flavonoids from Dendrophthoe pentandra (L.) Miq leaves involve the use of methanol as a solvent in maceration extraction methods. The presence of flavonoids was ascertained through color changes from green to yellow-green, yellow, and yellow-orange when subjected to AlCl3 5%, NaOH 10%, and Mg-HCl, respectively. Thin-layer chromatography using aluminum plates coated with silica gel F254 as the stationary phase and methanol-chloroform 4:1 (v/v) as the mobile phase was employed to separate the flavonoids. The method validation demonstrated strong linearity in the concentration range of 60-130 ppm for flavonoid standard solutions, with a correlation coefficient (r) of 0.998. The Limit of Detection (LOD) and Limit of Quantitation (LOQ) were determined to be 182.5 ng and 608.3 ng, respectively. Precision, expressed as Relative Standard Deviation (RSD), was found to be 5.1%, 2.8%, and 2.5% for concentrations of 80, 90, and 100 ppm, respectively. These RSD values were also less than 2/3 CV Horwitz, which were 5.5, 5.4, and 5.4. The method's accuracy was assessed through percent recovery values for each concentration (80, 90, and 100 ppm), which were found to be 102.46 ± 1.78%, 86.14 ± 1.74%, and 89.89 ± 1.44%. The flavonoid content in the dried coffee mistletoe powder was determined to be 1.404x10-2 ± 0.0007 mg per gram, with a water content of 8.7%.